Features of Administrative and Legal Regulation of Protecting Forestry Fund Land in Ukraine (Law and Safety, 2019)
The peculiarities of administrative and legal means for protecting forestry land of Ukraine have been considered. The issues of protecting forestry fund land in the context of the protection of forestry land have been researched. It has been found out that measures on protecting forestry land are divided into measures directly aimed at the protection of lands and measures related to forests protection. These measures constitute the content of the protection of forestry land.It has been noted that the structure of forestry land in the Forest Code of Ukraine is revealed through the indication on its composition: lands where forest areas are placed covered with forest vegetation; non-forest lands not covered by forest vegetation provided and used for forestry purposes.The following features of the land forest plot have been defined: it is a part of the forestry fund of Ukraine; it has defined boundaries; may be granted to a land user or land owner for forestry activities or may be withdrawn from a land user or land owner for forestry activities or other public needs.The basic feature of forestry fund land and non-forest areas has been clarified. It has been emphasized that non-forest lands are not included in the forestry fund of Ukraine as they are occupied by agricultural lands, water and marshes, facilities, communications, low-productive lands, etc., which are provided in due course and used for the needs of forestry activities.It has been concluded that the means of administrative and legal protection of forestry fund land of Ukraine are nowadays: quality management of agricultural land; organization and monitoring of forestry fund land of Ukraine; development of plans for the protection of forestry fund land of Ukraine, implementation of state control over the execution of measures, norms and rules for the protection of the forestry fund, etc.
Keywords: administrative and legal measures of protection; state control; state monitoring; forestry fund lands; timberland